Product liability under the Consumer Protection Act 1999 - Amin, Naemah (International Islamic University Malaysia, 1999)
Product liability law in Malaysia is now entering into a new era with the recent introduction of the Consumer Protection Act 1999 (hereinafter referred to as the Act). Part X of the Act introduces a new system of liability in respect of loss or damage caused by defective products similar to the system available in the United kingdom and other European countries. The new law offers the victims of defective products an additional remedy to existing remedies under the law of contract and tort of negligence. The purpose of this piece is to examine a new set of concepts introduced by the Act such as 'product', 'producer', 'defect' and the defences available to the defendant in order to assess the extent to which the new law realises its main objectives to improve the substantive position of the victims of defective products.